La rédactologie: méthodologie pour la rédaction professionnelle. Prémisses, acquis et perspectives - Vecchiato, Sara (Ponti/Ponts, 2022)
This article provides an overview of research on rédactologie, which emerged as the counterpart of Writing Studies in a network of French-speaking Canadian universities in the 1990s. Quebec-based researchers on rédactologie focus on professional writing, i.e. written production carried out for a client. The first part of the article presents the context of the development of professional writing: indeed, mass literacy has democratised the consumption of the written press, but it has also raised the question of access to information by the public. The awareness of how important it is for a text to be intelligible motivated the success of the Plain language movement, notably of French “Clear Language”, and of “Easy-to-read” texts. The second part of the article is devoted to the development of rédactologie in Quebec: it traces the foundation of writing labs and scientific societies, and the planning of university programmes of interest to local companies. In the third part, some major contributions of research on rédactologie are presented, such as a definition of textual clarity and that of customised writing. The article ends with a look at the diffusion of rédactologie in Europe and its relationship with translation.